(untitled) - Shafir, Gershon (Cambridge,New York, 2002)
This penetrating and timely study by two well-known scholars offers a theoretically informed account of the political sociology of Israel. The argument is set in its historical context as the authors trace Israel's development from the beginning of Zionist settlement in Palestine in the early 1880s to the Oslo accords in 1993, and finally to the recent Palestinian uprising. Against this background, they speculate on the idea of citizenship and what it means to be the citizen of a fragmented and ideologically divided society.
Keywords: Xã hội dân sự,Citizenship,Civil society,Công dân; Israel,Israel,Israel,Israel